A reference haplotype panel for genome-wide imputation of short tandem repeats - Shubham Saini (Nature Portfolio, 2018)
Short-tandem repeats (STR), similar to single nucleotide polymorphisms (SNP), contribute to complex traits, but their ascertainment by next-generation sequencing is costly. Here, Saini et al. provide a SNP+STR haplotype reference panel that allows imputation of STRs from SNP array data.